10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Growth hormone-secreting pituitary adenoma (GHPA) can cause excessive growth hormone production, which can lead to clinical symptoms such as acromegaly. Tumor stem cells (TSCs) are postulated to play a significant role in the development of GHPA. We performed RNA sequencing on human pituitary adenoma stem-like cells (hPASCs) and matched bulk tumors to map a differentiation protein-protein interaction (PPI) network. The function of the C-X-C motif chemokine receptor-4 (CXCR4) gene was tested in hPASCs and the GH3 cell line. The CXCR4-based 68Ga-pentixafor tracer was assessed by the positron emission tomography and computed tomography (PET/CT) scanning of GHPA patients. A total of 685 differentially expressed genes were identified between hPASCs and differentiated tumor cells. Four clusters of genes were predicted, each carrying distinct biological functions. CXCR4 was pinpointed as a potential hub gene, which significantly affected the self-renewal and differentiation of hPASCs, as well as the proliferation, invasion, and migration of GH3 cells. CXCR4 suppression decreased intra-tumoral angiogenesis and epithelial-to-mesenchymal transition (EMT). CXCR4-based 68Ga-pentixafor was a more adaptive tracer than 18F-FDG in diagnosing GHPA using PET/CT. This study provides a comprehensive genetic profiling of hPASCs and substantiates the critical role of CXCR4 in tumorigenesis, highlighting its potential in translational medicine.